PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP CORPORATE IMAGE DI KSPPS BMT NU JAWA TIMUR CABANG PAKONG - Qurratul Aini; Farid Firmansyah; Fahrurrozi (STIE Bakti Bangsa Pamekasan, 2021)
Corporate Social Responsibility can be used as a new marketing tool for companies if it is carried out sustainably. This study uses a quantitative approach with simple linear regression analysis techniques. The type in this research is primary data obtained through questionnaires. The respondents are customers from KSPP BMT NU Pakong Branch. The results showed that there was an effect of the application of Corporate Social Responsibility on Corporate Image at KSPP BMT NU Pakong Branch. 05, as well as a positive beta coefficient. From the results of the coefficient of determination (R2) using SPSS (Statistical for The Social Sciences) version 24, by looking at the R square of 0.419. This means that 41.9% of Corporate Image is explained through Corporate Social Responsibility at KSPP BMT NU Pakong Branch. From the simple linear regression equation (Y = a + bX), namely Y = 6.222 + 0.536X, where the value of the constant (a) Corporate Image is 6.222 shows that if the Corporate Social Responsibility variable is equal to zero (not considered), the Corporate Image is 6.222. unit and b = 0.536, it means that the coefficient of the Corporate Image variable is positive (0.536) indicating that if the Corporate Social Responsibility increases by 1 unit, the Corporate Image score will increase by 0.536 units.